Validation of an ICD-Based Algorithm to Identify Sepsis: A Retrospective Study - Diao ST; Dong R; Peng JM; Chen Y; Li S; He SH; Wang YF; Du B; Weng L (Risk Management and Healthcare Policy, 2023)
Shi-Tong Diao, Run Dong, Jin-Min Peng, Yan Chen, Shan Li, Shu-Hua He, Yi-Fan Wang, Bin Du, Li Weng On behalf of the China Critical Care Clinical Trials Group (CCCCTG)Medical Intensive Care Unit, State Key Laboratory of Complex Severe and Rare Diseases, Peking Union Medical College Hospital, Peking Union Medical College & Chinese Academy of Medical Sciences, Beijing, People’s Republic of ChinaCorrespondence: Li Weng, Medical Intensive Care Unit, State Key Laboratory of Complex Severe and Rare Diseases, Peking Union Medical College Hospital, Peking Union Medical College & Chinese Academy of Medical Sciences, 1 Shuai Fu Yuan, Beijing, 100730, People’s Republic of China, Email wengli@gmail.comBackground: Sepsis surveillance was important for resources allocation, prevention, and development of health policy.Objective: The aim of the study was to validate a modified International Classification of Diseases (ICD)-10 based algorithm for identifying hospitalized patients with sepsis.Methods: We retrospectively analyzed a prospective, single-center cohort of adult patients who were consecutively admitted to one medical ICU ward and ten non-ICU wards with suspected or confirmed infections during a 6-month period. A modified ICD-10 based algorithm was validated against a reference standard of Sequential Organ Failure Assessment (SOFA) score based on Sepsis-3. Sensitivity (SE), specificity (SP), positive predictive value (PPV), negative predictive value (NPV), and areas under the receiver operating characteristic curves (AUROCs) were calculated for modified ICD-10 criteria, eSOFA criteria, Martin’s criteria, and Angus’s criteria.Results: Of the 547 patients in the cohort, 332 (61%) patients met Sepsis-3 criteria and 274 (50%) met modified ICD-10 criteria. In the ICU setting, modified ICD-10 criteria had SE (84.47%), SP (88.57%), PPV (95.60), and NPV (65.96). In non-ICU settings, modified ICD-10 had SE (64.19%), SP (80.00%), PPV (80.33), and NPV (63.72). In the whole cohort, the AUROCs of modified ICD-10 criteria, eSOFA, Angus’s criteria, and Martin’s criteria were 0.76, 0.75, 0.62, and 0.62, respectively.Conclusion: This study demonstrated that modified ICD-10 criteria had higher validity compared with Angus’s criteria and Martin’s criteria. Validity of the modified ICD-10 criteria was similar to eSOFA criteria. Modified ICD-10 algorithm can be used to provide an accurate estimate of population-based sepsis burden of China.Keywords: sepsis, validation, International Classification of Diseases, administrative health data, identification